DAMPAK COVID-19 DAN VARIABEL MAKRO EKONOMI TERHADAP STABILITAS PERBANKAN SYARIAH DI INDONESIA - Masfiatun (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
This research is motivated by the growth of Islamic bank assets which is quitehigh in 2020, but Non-Performing Financing (NPF) has also increased. Theentry of Covid-19 in Indonesia in early 2020 is thought to have an impact on thestability of Islamic banks. In addition to Covid-19, the stability of Islamic banksis also inseparable from the conditions of several macroeconomic indicators.Therefore, this study tries to unravel whether Covid-19 and whatmacroeconomic indicators affect the stability of Islamic banks. The data used inthis study are monthly time series from 2016-2020. The results of this studyindicate that Covid-19 has a negative effect on the stability of Islamic bankswhile the Growth of Gross Domestic Product (GDP) has a positive effect.